Yakuglas' Legacy : The Art and Times of Charlie James - Hawker, Ronald William, 1963- (Book collections on Project MUSE., 2016)
Charlie James (1867-1937) was a premier carver and painter from the Kwakwaka'wakw First Nation of British Columbia. Also known by his ceremonial name Yakuglas, he was a prolific artist and activist during a period of severe oppression for First Nations people in Canada. Yakuglas' Legacy examines the life of Charlie James. During the early part of his career James created works primarily for ritual use within Kwakwaka'wakw society. However, in the 1920s, his art found a broader audience as he produced more miniatures and paintings. Through a balanced reading of the historical period and James' artistic production, Ronald W. Hawker argues that James' shift to contemporary art forms allowed the artist to make a critical statement about the vitality of Kwakwaka'wakw culture. Yakuglas' Legacy, aided by the inclusion of 123 colour illustrations, is at once a beautiful and poignant book about the impact of the Canadian project on Aboriginal people and their artistic response.--